'The Faithful Remnant of the True Church of England': Susanna Hopton and the Politico-Theology of the Nonjuring Schism. (7th January 2021) - Lewis, Simon
Abstract: Susanna Hopton (1627–1709) is best known for her devotional literature, and her association with the Anglican clergyman and poet, Thomas Traherne (1636–74). Significantly less scholarly attention, however, has been devoted to her role and influence as a Nonjuring theologian. By analysing some neglected letters and publications, this paper not only illuminates Hopton's independence as a theological controversialist but also explores her role as an evangelist for the Nonjuring cause. Fresh evidence is advanced to elucidate the ways in which Hopton's theological trajectory differed from those of Nonjuring divines. Furthermore, by exploring Hopton's friendship with the prominent Nonjuring divine, George Hickes (1642–1715), this paper enhances our knowledge of clerical perceptions of women theologians during the late seventeenth and early eighteenth centuries.